Catalytic effect of sodium components on the microstructure and steam gasification of demineralized Shengli lignite char. (13th April 2017) - Lu, Rongrong; Wang, Jie; Liu, Quansheng; Wang, Yan; Te, Gusi; Ban, Yanpeng; Li, Na; Zhang, Xiaorong; He, Runxia; Zhou, Huacong; Zhi, Keduan
Abstract: The catalytic effect of sodium on the demineralized Shengli (SL + ) lignite char microstructure and the performance of steam gasification were studied. Various sodium compounds including NaNO3, CH3 COONa, Na2 CO3 and NaOH were loaded on the demineralized coal samples, respectively, and the steam gasification was tested on the fix-bed reactor. The char samples were characterized by X-ray diffraction (XRD), Raman, X-ray photoelectron spectroscopy (XPS) and FT-IR spectroscopy. Experimental results showed that sodium hydroxide loaded samples exhibited the highest gasification reactivity among the coal samples prepared. With the increase of the alkalinity of sodium compounds, the carbon crystallite structure tended to be disordered. In the process of pyrolysis, the introduction of sodium species promoted the ring-opening and polycondensation process of the chemicals in the coal samples. The possible reaction mechanism might be inferred that the sodium ions may replace the hydrogen ions in the oxygen-containing functional groups to form sodium phenolate intermediate, which may be critical for the catalytic effect of sodium species during gasification. It was speculated that the ring-opening of the condensation aromatic nucleus was the rate-limiting step in the whole process of gasification. Highlights: Pickling minerals off significantly reduced the reactivity. Adding sodium significantly increased the gasification reactivity. Mechanism that the action of oxygen containing functional groups and sodium is the catalytic core.